Hubungan Aktivitas Fisik dengan Kadar Gula Darah Sewaktu pada Lanjut Usia Penderita Diabetes Mellitus - Nazwa Aura Salsabila; Kartinah Kartinah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Long-term illness diabetes mellitus results from the pancreas failing to generate enough insulin, a hormone controlling blood glucose or glucose levels. Aging is a regular process in the life cycle marked by decreased physical capacity and decline in body. Directly affecting the capacity of elderly people to carry out daily activities, this decreased muscle mass and reduced flexibility result from their reduced capacity. Managing diabetes depends on physical activity since any kind of movement calls the body to use more energy. A cross-sectional design and a quantitative methodology employing a correlation design were applied in this study. The GPAQ (Global Physical Activity Questionnaire) was used to check random blood sugar (GDS) and evaluate physical activity. Ninety-one participants who came to the Kartasura Community Health Center and fulfilled the inclusion and exclusion criteria were the sample gathered for this investigation. Spearman's rank test with a P-value of 0.000 (p<0.05) and a correlation value of r of (-0.449) was used to analyze the data. The results of the analysis revealed that most of respondents—56%—had moderate physical activity and 51% had uncontrolled blood sugar levels. Given these correlation values, the results suggest a relationship between blood sugar levels and physical activity levels in diabetics mellitus patients at the Kartasura Community Health Center.